The Influence of Price, Product Quality, and Product Diversity on the Purchase Decision of Galvanized Battery Cages at CV Baja Jaya Mandiri - Sodakh, Lisa Angelina; Djoko Soeprijatno, Edy (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research purposes: The aim of this research is to examine how Price, Product Quality, and Product Variety affect the buying choices related to Galvanized Battery Cages at CV Baja Jaya Mandiri. Research technique: This investigation employs a numerical strategy with a cause-and-effect research style, collecting original data via surveys given to 40 participants. The evaluation applies methods of multiple linear regression. Study Outcomes: The analysis reveals that Price, Product Quality, and Product Variety positively influence Purchasing Decisions, both separately and collectively. As a result, CV Baja Jaya Mandiri should work on enhancing product quality, making prices more competitive, and broadening product options to draw in more customers and fulfill the requirements of laying hen farmers. Significance for Stakeholders/Policymakers: Comprehending how these elements interact is anticipated to give producers better knowledge of the desires and necessities of galvanized battery cage users, leading to more successful marketing approaches.. Research limitations :It is difficult to measure the impact of price, quality, and variety separately because they are interrelated. Consumers may evaluate product quality and price simultaneously, and product variety factors may also influence their views on price and quality.